Implementasi Hybrid Learning Dalam Proses Pembelajaran Di Universitas Terbuka Madiun - Septya Azhari Putri Wardana (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This research explains the implementation of hybrid learning in the learning process at open universities with the aim of finding out how hybrid learning is implemented in the educational process at open universities. The research method used is a qualitative method using interview techniques. Here we conducted interviews with two tutor lecturers from the Open University. From the results of the interviews conducted, a result was obtained, namely the use of hybrid learning at the Open University using E-learning or Electronic Learning is a concept in the learning process using information and communication technology (ICT), namely using internet networks. Distance learning at open universities is known as tuton (online tutorial). The positive thing about using hybrid learning is that the implementation of learning is more flexible. In evaluating learning, lecturers give assignments to students with a deadline of 2 weeks, apart from that, final semester exams are also held at open universities.